DIMENSI PEMILU DALAM SISTEM DISTRIK DAN PROPORSIONAL - Diyar Ginanjar; Fauziah Hanifah; Uu Nurul Huda (Khazanah Multidisiplin, 2020)
The electoral system is regulated in statutory regulations containing three main variables, namely voting, electoral district, and electoral formula. As stated in the Election Law, the objective of the electoral system is to exercise people's sovereignty. A provision which is in line with the universal democratic principle of the rulers directs this goal to build legitimacy for a stable and strong government in mobilizing the masses. democratically Election, namely balancing these operational objectives with their use as a means of fighting for the interests of the people through political participation and political socialization